Analisis Persepsi Mahasiswa PGSD terhadap Penggunaan Platform Pembelajaran SiPeDar - Elyas Djufri; Heri Maria Zulfiati; Alfat Khaharsyah; Ida Megawati; Bherrio Dwi Saputra; Dewi Anggreini; Bestiana Nizhomi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This research aims to analyze the perception of Elementary School Teacher Education Program (PGSD) students regarding the use of the SiPeDar Learning Platform in the academic environment. The research method employed was a survey using a questionnaire as the primary instrument. The respondents in this study were active PGSD students who used SiPeDar in their learning processes. The main findings of this research indicate that 90% of PGSD students at UST Yogyakarta have a good understanding of SiPeDar usage and feel comfortable operating it. Factors such as the availability of technological resources and support from instructors also have a positive impact on students' perceptions of the quality and effectiveness of SiPeDar, with 95% acknowledging this influence. Furthermore, a significant majority of students expressed satisfaction with the use of SiPeDar in the learning process. The results of this research can provide valuable insights to educational institutions and developers of similar learning platforms to enhance the use of SiPeDar and support more effective distance learning in the future.